Design and implementation of micro-power temperature to duty cycle converter using differential temperature sensing. Issue 6 (June 2015) - Chouhan, Shailesh Singh; Halonen, Kari
Abstract The CMOS based temperature detection circuit has been developed in a standard 180 nm CMOS technology. The proposed temperature sensor senses the temperature in terms of the duty cycle in the temperature range of −30 °C to +70 °C. The circuit is divided into three parts, the sensor core, the subtractor and the pulse width modulator. The sensor core consists of two individual circuits which generates voltages proportional (PTAT) and complementary (CTAT) to the absolute temperature. The mean temperature inaccuracy (°C) of PTAT generator is −0.15 °C to +0.35 °C. Similarly, CTAT generator has mean temperature accuracy of ±1 °C. To increase thermal responsivity, the CTAT voltage is subtracted from the PTAT voltage. The resultant voltage has the thermal responsivity of 6.18 mV/°C with the temperature inaccuracy of ±1.3 °C. A simple pulse width modulator (PWM) has been used to express the temperature in terms of the duty cycle. The measured temperature inaccuracy in the duty cycle is less than ±1.5 °C obtained after performing a single point calibration. The operating voltage of the proposed architecture is 1.80±10% V, with the maximum power consumption of 7.2 μW.